Tackling hearing loss to improve the care of older adults. (18th January 2018) - Blustein, Jan; Weinstein, Barbara E; Chodosh, Joshua
Abstract : Many older adults have difficulty understanding speech in acute healthcare settings owing to hearing loss, but the effect on patient care is often overlooked, argue Jan Blustein and colleagues